Discovery of a dense molecular cloud towards a young massive embedded star in 30 Doradus - Rubio, M. (2009)
Context. The 30 Doradus region in the Large Magellanic Cloud is one of the most outstanding star-forming regions of the Local Group and a primary target for studying star formation in an environment of low metallicity. Aims. To obtain a more complete picture of the cool gas that has not yet been consumed or dispersed, we searched for line emission from molecular clouds that could be associated with molecular hydrogen emission detected in the region. Methods. We obtained a high sensitivity 12CO J = 2–1 map with the 15-m SEST telescope, complemented by pointed observations of 13CO J = 2–1 and CS J = 2–1. Results. We report the discovery of a dense molecular cloud towards an embedded young massive star at ∼20 (∼5 pc, at the distance of 50 kpc) northwest of R136, the compact massive central stellar cluster powering 30 Doradus in the LMC, which could be triggering star formation in the surrounding molecular clouds. We derived a molecular mass of 104 M , a linear radius of 3 pc, as an upper limit, and a mean density of 103 cm−3 for the cloud. The detection of the CS J = 2–1 emission line indicates higher densities, ∼106 cm−3. The dense molecular cloud is associated with molecular 2.12 μm H2 emission. We suggest that the observed molecular gas could be the remains of dense molecular material surviving the action of strong UV fields and winds in which the young massive star has formed.